The Effect of STEAM Integration on Middle School Music Education - Kim, Chanmi; Auh, Yoonil (Researchparks Publishing, 2024)
The research aims to assess the impact of integrating STEAM (Science, Technology, Engineering, Arts, Mathematics) learning into middle school music education in Korea. It investigates the integration of STEAM in music education and identifies factors influencing student motivation. Statistical analysis reveals that STEAM integration positively affects student motivation, attendance, and participation. A significant difference in motivation levels was found between control and experimental groups, with the experimental group showing higher motivation. The findings suggest that STEAM learning enhances student engagement and enthusiasm, particularly in the working details of music, leading to improved competencies and motivation.